Novel Thymoquinone Derivative TQFL28 Inhibits Triple-Negative Breast Cancer (TNBC) Invasiveness In Vitro and In Vivo - Jiayue He; Hui Zou; Chunli Wei; Jun Du; Ting Xiao; Ting Li; Ali El-Far; Jingliang Cheng; Junjiang Fu; Xiaoyan Liu (Current Issues in Molecular Biology)
Although thymoquinone (TQ) has been reported as an anti-tumor small molecule well investigated in numerous tumors. In this study, we designed and synthesized a novel TQ derivative, TQFL28, with a molecular formula of C20H23NO2. TQFL28 showed stronger cytotoxicity or anti-proliferative activities against triple-negative breast cancer (TNBC) cell lines (BT549, MDA-MB-231, or 4T1) than TQ but is lower in the normal mammary epithelial cells, MCF10A. TQFL28 exhibited lower IC50 values toward BT549 (38.78 ± 1.589) and MDA-MB-231 (39.63 ± 1.598) cells compared to TQ, indicating its efficacy for TNBC cytotoxicity. TQFL28 inhibited the growth, migration, and invasiveness of TNBC cells of 4T1 and BT549 in vitro and tumor progression and metastasis in a 4T1 allograft animal model in vivo. Moreover, TQFL28 presents lower toxicity than TQ in mice, showing a 7-day half-lethal dose (LD50) of 59.43 mg/kg (41.6–83.6, 95% confidence interval). Altogether, our study obtained. In addition, TQFL28 induced a significant reduction in tumor volumes in the mouse model in comparison to the vehicle group. TQFL28, a novel small molecule, has a superior inhibitory effect and lower toxicity on TNBC both in vitro and in vivo. Thus, TQFL28 might have potential as a therapeutic small molecule for breast cancer, especially in TNBC.